A Review on “Anjan” Hardwickia binata Roxb.: Its Phytochemical Studies, Traditional Uses and Pharmacological Activities - Shingade, SP; Kakde, RB (Pharmacognosy Reviews)
Hardwickia binata commonly known as “Anjan” belonging to the family Caesalpiniaceae is a handsome medium or large deciduous ornament tree with graceful drooping branch lets is represented by a single species Hardwickia binata Roxb. It is used in folklore medicines for various ailments including diarrhea, leprosy, worm’s infection, indigestion, leucorrhoea, chronic cystitis, gonorrhea, cancer, gram negative and gram positive bacteria and fungi. The parts of plant used as roots, leaves, bark, seed, wood, Husk. The review describes therapeutic efficacy of the leaves, seed, root, husk and its extracts and isolated compounds in different aliments such as antimicrobial, analgesic, antifungal, antibacterial, cardio protective, anti-inflammatory, antitumor and DNA polymerase β inhibition properties of Hardwickia binata were reported. A preliminary Phytochemical screening show that it comprises mainly phenolic compound, saponins, flavonoids, glycosides and tannins, carbohydrate, protein, amino acids, steroids, lipids, quinones, volatile oil, fats and fixed oil. Bioactivity-guided fractionation of an active methyl ethyl ketone extract of Hardwickia binata reported to the isolation of a potent inhibitor, named as Harbinaticacid, a novel diterpenoid and its potency as DNA polymerase β inhibitor. Root bark exudates has been traditionally used to cure breast cancer by Malayali tribes of Chitteri hills. The ethanolic leaf extracts of Hardwickia binata Roxb (Caesalpinaceae) showed a broad-spectrum of activity against both gram-positive and gram-negative bacteria and were screened for antibacterial activity. This systematic review aims to provide information regarding distribution, Morphology, Phytochemical Constituents, Traditional uses and also describes various pharmacological activities reported on the plant Hardwickia binata which may help in future research to improve human health care.
Keywords: Hardwickia binata Roxb.; Anticancer; Antibacterial; Antifungal; DNA polymerase β inhibitor; GC-MS; FTIR.